Giant liposarcoma of esophagus: a rare case report - Qingjiao Li; Si Chen; Yanchun Li; Zhihong Chen; Yu Liu; Wei Guo (BMC, 2023)
Abstract Background Liposarcoma is a malignant mesenchymal tumor that most commonly involves the retroperitoneum and lower extremities. However, liposarcoma of esophagus has been rarely reported in the literature. Case presentation We report a case of a 46-year-old man with complaint of intermittent dysphagia for 6 years, accompanied with paroxysmal vomiting of pedicled tumor to the mouth. Imaging studies showed a huge mixed density lesion in the middle esophageal lumen. Surgical resection of the tumor was performed through an external cervical approach. Microscopically, the tumor was composed of mature adipocytes in normal adipose tissue prominently intersected by sparsely cellular fibrous septa containing atypical, enlarged spindle cells with hyperchromatic nuclei. Immunohistochemically, the tumor cells were positive for Vimentin, S-100, CD34 and MDM2. Besides, fluorescence in situ hybridization (FISH) analysis indicated the presence of amplification involving MDM2 gene. The patient was diagnosed as having esophageal well-differentiated liposarcoma and recovered well after the operation. Conclusions Esophageal liposarcoma is an extremely rare tumor. Due to the nonspecific clinical manifestation and lack of experience, it is challenging to make a clear diagnosis before operation. Definite diagnosis of esophageal liposarcoma depends on histopathology, immunohistochemistry and molecular analysis.